2021
DOI: 10.1080/21645515.2021.1872341
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the evidence behind the comparable impact of the pneumococcal conjugate vaccines PHiD-CV and PCV13 on overall pneumococcal disease

Abstract: The worldwide implementation of pneumococcal conjugate vaccines (PCVs) in children has reduced the overall pneumococcal disease burden. Two PCVs are widely available for infant vaccination: the pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) and the 13-valent PCV (PCV13). While these PCVs differ in serotype composition (PCV13 includes polysaccharides of serotypes 3, 6A and 19A; PHiD-CV does not), their impact on the overall pneumococcal disease burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Data from European countries show that the introduction of mandatory pneumococcal vaccination has reduced the incidence of IPD. This effect was demonstrated for both PCV10 and PCV13 [50,51]. The difference is seen in the case of serotypes 6C and 19A, where PCV10 offers no significant protection.…”
Section: Discussionmentioning
confidence: 90%
“…Data from European countries show that the introduction of mandatory pneumococcal vaccination has reduced the incidence of IPD. This effect was demonstrated for both PCV10 and PCV13 [50,51]. The difference is seen in the case of serotypes 6C and 19A, where PCV10 offers no significant protection.…”
Section: Discussionmentioning
confidence: 90%
“…Although this may indicate that PCV13 may provide better protection, empirical data has shown that PCV13 has little to no protection against serotype 3 and has similar levels of serotype replacement as PCV10. (39,40) This higher predictions in serotype coverage for PCV13 may therefore not translate to larger IPD reductions. Our predictions show that SII-PCV has similar coverage to PCV10, and we attribute this to differences in carriage prevalence and IC of the included and excluded serotypes.…”
Section: Discussionmentioning
confidence: 99%